Implementing administrative apparatus reform for effectiveness and efficiency in the new era - Nguyen Thi Kim Chung (Journal of State Management, 2025)
This article analyzes the process of reforming Vietnam’s state administrative apparatus inaccordance with Resolution No. 18- NQ/TW dated October 25, 2017, issued by the Party CentralCommittee, which aims to build a streamlined administrative system that operates effectively andefficiently. After reviewing the current status of administrative organization restructuring, theauthor highlights the achievements in consolidating administrative units, reducing staffing levels,reorganizing public administrative and service units, and promoting rational decentralizationbetween levels of government. The article also proposes five key solution groups to furtherenhance the effectiveness of the administrative apparatus reform. It affirms that reform is notmerely about downsizing but fundamentally about transforming governance thinking - towardsbuilding a modern administrative system that is responsive to the context of digital transformationand international integration.